2022
DOI: 10.1016/j.ab.2021.114541
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent and colorimetric RT-LAMP as a rapid and specific qualitative method for chronic myeloid leukemia diagnosis

Abstract: The detection of BCR-ABL1 mRNA transcripts is essential to molecular chronic myeloid leukemia (CML) diagnosis. In most cases, the RT-qPCR technique is performed as the gold standard diagnosis tool for clinical cases. However, this method requires expensive reagents and equipment, such as a real-time thermal cycler, probes and master mix. Consequently, the development and validation of simple and lowcost methods are essential for a rapid CML diagnosis in less specialized and equipped centers. In this study, we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…S5 and Table S3, ESI†). 14,21–28 Furthermore, among the mixed samples with different concentrations of RNA targets, we observed that the LOD of the samples containing EML4-ALK V1 in 10 ng total RNA was 0.5% (Fig. 2D).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…S5 and Table S3, ESI†). 14,21–28 Furthermore, among the mixed samples with different concentrations of RNA targets, we observed that the LOD of the samples containing EML4-ALK V1 in 10 ng total RNA was 0.5% (Fig. 2D).…”
mentioning
confidence: 87%
“…Fig.2A-Cshowed a good linear relationship between the peak of fluorescence spectra and input concentrations (R 2 = 0.993). The proposed CATCH approach enabled EML4-ALK V1 detection in the femtogram range, which has been improved by four orders of magnitude compared with the CATCH assay without subsequent CHA amplification, and also had a better analytical performance than other methods (Fig.S5and TableS3, ESI †) 14,[21][22][23][24][25][26][27][28]. Furthermore, among the mixed samples with different concentrations of RNA targets, we observed that the LOD of the samples containing EML4-ALK V1 in 10 ng total RNA was 0.5% (Fig.2D).We also evaluated the detection capability of the proposed approach by a standard recovery experiment and repeatability study.…”
mentioning
confidence: 99%